Problematic of Implementing Asesmen Nasional in Elementary School - Yusella, Yeni; Mahanal, Susriyati; Mashfufah, Aynin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to analyze the problems of Asesmen Nasional in elementary schools. The type of research used in this study is qualitative descriptive research. This study uses analytical techniques from Miles, and explains Huberman which consists of Data Collection; Data Reduction; Data View; and drawing conclusions/verifications. The results showed that: (1) Problems first arise in schools when the distribution or announcement of the names of students who must take literacy and numeracy tests is submitted to the school. (2) The second problem is that students when the AKM numeracy literacy test is carried out, learning is still running with the fifty-fifty model (50-50), (3) The last problem that arises is when the implementation of taking the test in the Computer Laboratory. Furthermore, the design of solutions when implementing the Asesmen Nasional of fifth grader, including: (1) the efforts made by the next teacher are to provide literacy and numeracy materials in the form of books and questions that have been given when students are of fourth grader. (2) Regarding students’ difficulties with literacy questions whose reading is too long and understanding numeracy questions that require a high level of thinking, the teacher provides guidance as long as the students conduct trials and do the practice questions. (3) The next effort made by the teacher is to provide literacy and numeracy materials in the form of books and questions that have been given when students as fourth grader. (3) Furthermore, the last problem that arises in schools is the occurrence of an error system and having to re-login. This can be anticipated with the teacher’s instructions to record the results of the answers that have been done.